Dynamic life cycle assessment of straw-based renovation: A case study from a Portuguese neighbourhood. Issue 4 (November 2020) - Göswein, V; Pittau, F; Silvestre, J D; Freire, F; Habert, G
Abstract: Action is needed to mitigate climate change. As the building sector is one of the main contributors to energy consumption, renovation of existing buildings is a key strategy. However, for a drastic greenhouse gas emissions (GHG) reduction, sensible material solutions are required. Bio-based products seem to be a promising alternative thanks to carbon sequestration in the new biomass, which needs to be regrown for substitution. The conventional life cycle assessment (LCA) framework seems unsuited to model temporal emissions and carbon uptake of such solutions. Dynamic LCA (DLCA), which models temporal aspects, is more appropriate to evaluate the environmental performance of bio-based products. Moreover, the different dynamic drivers of urban building stocks should be included to allow for informed material choices. A new methodology is proposed, integrating DLCA with material flow analysis (MFA) considering a dynamic renovation rate. The global warming potential over time of the thermal retrofit of a Lisbon neighbourhood with a straw-based technology is assessed. The results highlight the importance of the end of life scenario, greatly influencing the results in the mid- to long term. Increased renovation rates can yield higher carbon storage benefits. However, if accompanied by technological solutions that rely on carbon intensive materials, e.g. finishing, this can lead to increased embodied carbon emissions in the transition period.